(untitled) (Research, Society and Development, 2024)
The objective of this article is to present a review of the importance of humanized communication between health professionals and parturients as a fundamental element for improving the birth experience and preventing obstetric violence. Studies on communication practices in the context of childbirth were analyzed through a narrative review of the literature. The results indicate that clear and empathetic communication significantly reduces the stress and anxiety levels of pregnant women, in addition to promoting greater satisfaction with the service. Concluding that the adoption of continuous dialogue strategies and the implementation of birth plans are important to ensure more respectful and woman-centered care, contributing to the reduction of obstetric violence practices.